Vodní měkkýši Labe mezi Pardubicemi a Hřenskem - Luboš Beran (Malacologica Bohemoslovaca, 2005)
Aquatic molluscs of the Elbe River between Němčice (near Pardubice, Eastern Bohemia, Czech Republic) and Hřensko (Northern Bohemia, Czech Republic) at 27 localities were investigated from 1994 to 2004. Altogether 40 species (24 gastropods, 16 bivalves) from 77 species known on the territory of the Czech Republic were found at sites under study. A gradual invasion of 6 non-native species (Potamopyrgus antipodarum, Physella acuta, Menetus dilatatus, Ferrissia clessiniana, Corbicula fluminea) and an extinction of another species (Theodoxus fluviatilis, Planorbis carinatus, Unio crassus, Pisidium amnicum) were documented in comparison with historical records. Rare mussel Pseudanodonta complanata and rare pea mussel Pisidium moitessierianum were found at several localities under study and these finds document survival of these bivalves in the Elbe River. Molluscan communities of particular localities were most often usually compounded from species Viviparus viviparus (downstream of loc. 9), Bithynia tentaculata, Radix auricularia, Radix ampla, Unio pictorum, Anodonta anatina, Corbicula fluminea (downstream of loc. 8), Sphaerium rivicola (downstream of loc. 7), Sphaerium corneum s. lat., Pisidium supinum, Dreissena polymorpha.